Determination of Work Experience and Work Supervision on Job Rotation - Xi Hexan (Journal of Accounting and Finance Management, 2021)
Research on the determination of work experience and work supervision of work rotation is a scientific article of literature within the scope of human resource management. The object of this study is to investigate the influence of work experience and work supervision on work rotation. The purpose of this study is to determine the influence between variables. The research method uses qualitative methods, which analyze each variable. The results of this study are: 1) Work experience affects work rotation, meaning that with relevant and much work experience, workers will have a high chance of job rotation. So that those who have much experience it is possible to have a high position of position compared to those who do not have little experience or experience; 2) Work supervision affects Job rotation, meaning that the employee's work supervision ability will have an impact on employee work rotation; and 3) Work experience affects work supervision, This means that with the high flying hours of employees, it will have a positive impact on the ability of employees to supervise work.